Delineating the physico-chemical, structural, and water characteristic changes during the deterioration of fresh noodles: Understanding the deterioration mechanisms of fresh noodles. (1st February 2017) - Li, Man; Ma, Meng; Zhu, Ke-Xue; Guo, Xiao-Na; Zhou, Hui-Ming
Highlights: Structural and molecular changes occurred in fresh noodles during deterioration. Proteins and starch were partially depolymerized with progression of deterioration. Original noodle structure was damaged and water–solid interactions were weakened. The TPC, L ∗ value, and pH can indicate the deterioration of fresh noodles. Abstract: In this study, changes in fresh noodles during storage were evaluated at the physico-chemical, structural, and molecular levels. An increase in TPC and decrease in L ∗ value mostly occurred during the first 24 h; the pH value significantly decreased ( P < 0.05) and proteins were partially depolymerized with the deterioration of fresh noodles, as evidenced by free amino acid determination and SDS-PAGE. Changes were also detected in the pasting and viscosity properties of the starch component. Moreover, the water sorption isotherm of fresh noodles decreased during storage, and the NMR transverse relaxation peak shifted right with an increased peak area between 10 and 100 ms. MRI images showed that with increased storage time, the original structure was damaged and water distribution became non-uniform and migrated to the surface. TPC, pH, and L ∗ value were selected as the visualized parameters to characterize the fresh noodle deterioration, based on the correlation and factor analyses.